What if there were no new antibiotics? A look at alternatives. Issue 12 (1st December 2016) - Rello, Jordi; Bunsow, Eleonora; Perez, Antonio
ABSTRACT: Introduction : Bacterial resistance to antibiotics is increasing worldwide, due to the emergence of multidrug-resistant strains. With this panorama, there is a serious danger that we may be entering the 'post-antibiotic era'. Areas covered : We assess why so few new classes of antibiotics have been developed in the past years and discuss a variety of treatments that may be able to replace antimicrobials: monoclonal antibodies, bacteriophages, stem cells and anti-virulence agents such as liposomes. Expert commentary : There are a series of economic, scientific-research and regulatory reasons for the scarcity of new antimicrobials. New approaches are needed to combat infections. Innovative strategies like Eco-Evo drugs and innovative delivery methods such as aerosol or nanoparticle administration require a new management paradigm, in combination with rapid molecular diagnostic tests. Biopharma, clinical researchers, regulatory agencies, governments and investors must work together in the attempts to achieve effective treatment for infections caused by MDR organisms.